Harnessing the Power of Viral Marketing for Social Justice: A Netnographic Study of Netflix's Ice Cold Documentary - Salsabela, Kamila; Sabri; Mei, Tian (CHANNEL: Jurnal Komunikasi, 2024)
Viral marketing is word-of-mouth advertising that spreads quickly via online channels and can potentially have far wider effects than just commercial ones. This paper examines how viral marketing can be used to advance social justice by utilizing its ability to make social networks that motivate mass action. To create social justice, the goal is to examine how social media and viral marketing have affected the success of the Netflix documentary Ice Cold. Employing a netnography methodology and descriptive qualitative, data is gathered using a data site. Centered on examining the four elements of the viral marketing technique on social media: content, behavioral characteristics, social network structure, and seeding strategy. The result is emotional triggers and criticism forming the presence of high emotional activation resulting in the social connectivity of the audience that creates the tag and signature of petitions as the realization of social justice. Recommendations for marketing practitioners to create seeding strategies through current issues and social movements that are not just about profit-based marketing.